Analisis Gaya Kepemimpinan Kolaboratif Dalam Menghadapi VUCA Era - Marezka; Muthia; Kevin Ginaldo; Dio Pratama; Afmi Apriliani (KARIMAH TAUHID, 2022)
Leadership is the foundation of the establishment of an organization. which is the impact of unstoppable advances in technology and science, a person's leadership plays an important role in the sustainability of an organization. In facing an uncertain era or the VUCA Era, innovation is certainly needed from every aspect, including in terms of leadership. Not limited to working together, but also collaborating in solving problems together through leadership carried out by a group of people. The method used is a qualitative method with a qualitative descriptive approach, so that the research does not use certain variables. Data collection through literature studies was collected from various references such as journals. What was found in the results and discussion in this study was that researchers found that a collaborative leadership style was needed to solve the same problems experienced by a group of organizations so that it was not just cooperation but the unification of concepts in achieving common goals.